PENGEMBANGAN SISTEM INFORMASI JOB RECORD DAN PENILAIAN KINERJA KARYAWAN PADA PT. TRAKTOR NUSANTARA BANDAR LAMPUNG - Astria Hijriani; febi eka febriansyah; fitriana rahmawati (Universitas Lampung, 2015)
Job Record is the reference of Worker Performance Appraisal process where maximum or not the performance worker on certain period will be determined. The Development of Job record and worker performance appraisal information system with apply XML web service as method to exchange information between one and the other domains. With Web Service into information system could be handle business process that is recruitment, job record, worker performance appraisal, and payroll system. The resulting of exchange the information that is information of employees, overtime, and incentive. The implemented of this information system using PHP programming language and MySQL database and web service method using XML programming language. The result of Black Box testing showed that this The development of Job record and worker performance appraisal information system has been successfully created as the users need.